2003
DOI: 10.1051/0004-6361:20030207
|View full text |Cite
|
Sign up to set email alerts
|

Box simulations of rotating magnetoconvection

Abstract: Abstract. Various effects of penetration in rotating magnetoconvection are studied by means of three-dimensional numerical simulations employing the code NIRVANA. A local, 2-layer model is applied dividing the computational domain (which is a rectangular box placed tangentially on a sphere at latitude 45• ) in an unstable polytropic region on top of a stable polytropic region. Different realizations of convection are examined parameterized by Taylor numbers Ta = {0, 6×10 4 , 6×10 5 } and magnetic field strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 18 publications
5
38
1
Order By: Relevance
“…(Ossendrijver et al 2002;Käpylä et al 2006a) and other diagnostics (e.g. Nordlund et al 1992;Tobias et al 1998Tobias et al , 2001Ziegler & Rüdiger 2003). However, this result is obtained for test fields for which k/k 1 = 1, whereas the imposed field results use a uniform field with k/k 1 = 0.…”
Section: Resultsmentioning
confidence: 89%
“…(Ossendrijver et al 2002;Käpylä et al 2006a) and other diagnostics (e.g. Nordlund et al 1992;Tobias et al 1998Tobias et al , 2001Ziegler & Rüdiger 2003). However, this result is obtained for test fields for which k/k 1 = 1, whereas the imposed field results use a uniform field with k/k 1 = 0.…”
Section: Resultsmentioning
confidence: 89%
“…Furthermore, the relative stability parameter S showed an S −1/4 dependence on the penetration distance implying the existence of a thermal adjustment region in the lower stable layer rather than a nearly adiabatic penetration zone. Ziegler & Rüdiger (2003) and Käpylä et al (2004), using their 3D MHD codes also found that, as a general feature, the overshooting at the bottom decreases as a function of increasing rotation at a given latitude. Browning et al (2004) performed three-dimensional simulations of core convection within A-type stars at a range of rotation rates.…”
mentioning
confidence: 89%
“…It has been argued that there the strong flux tubes are highly buoyant so that it is difficult for them to resist in the convection zone. However, the numerical simulations which are now possible lead to the opposite phenomenon: the mean magnetic flux is pumped downwards (Dorch & Nordlund 2001;Thomas et al 2002;Ossendrijver et al 2002;Ziegler & Rüdiger 2003). It seems indeed as would the downward pumping of the magnetic field be the most prominent feature of the rotating magnetoconvection (Nordlund et al 1992).…”
Section: Introductionmentioning
confidence: 96%
“…It seems indeed as would the downward pumping of the magnetic field be the most prominent feature of the rotating magnetoconvection (Nordlund et al 1992). On the other hand, the penetration depth of the overshooting convection into the stable region below the convection zone appears to be very small (see Ziegler & Rüdiger 2003). Moreover, the transition region itself where the differential rotation rapidly becomes uniform (the tachocline) appears to be hydrodynamically unstable (Arlt, Sule & Rüdiger 2005).…”
Section: Introductionmentioning
confidence: 99%